EFEKTIVITAS TERAPI KOMPLEMENTER BERUPA PEMBERIAN KOMPRES HANGAT PADA REMAJA DENGAN DISMENORHEA DI DESA MALEI - Rasiman, Noviany Banne; Chely Veronica Mauruh; Nuraliah; Greyzela Mantadji (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
Adolescence is a period where a child experiences physical, hormonal and sexual changes that can initiate the reproductive process. Based on the results of interviews conducted with teenagers in Malei Village, some said that during menstruation they felt menstrual pain which sometimes interfered with their activities. The aim of this research is to find out the effectiveness of complementary therapy with warm water compresses for dysmenorrhea in teenagers in Malei Village. This is a quantitative research using a pre-experiment with a pre-test-post-test one group design. The Data using univariate and bivariate analysis. The sample in this research consisted of 32 teenagers. The sampling technique uses purposive sampling. The research results showed that the average pain of respondents before being given a warm compress was 56.3% on a moderate scale, the average pain of respondents after being given a warm compress was 90.6% on a mild scale. There was a difference before and after the warm compress was applied with P = 0.000 (p < 0.05). The conclusion is that complementary therapy with warm water compresses is effective in reducing dysmenorrhea in teenagers.